ENHANCEMENT OF ACTIVE POWER FLOW CAPACITY OF A TRANSMISSION LINE USING STATCOM MODEL - Ninad M. Bhumkar; Mahadev S. Patil (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Today the transmission line has many important considerations such as voltage drop, line losses and efficiency of transmission, which is needed to be taken into consideration. A voltage drop of the transmission line is totally depending on resistance and inductance of transmission line. The overall resistance of transmission line causes the power loss. STATCOM is a device which is used for to control the voltage regulation of the transmission line. Static compensation is the solution on voltage drop and power factor reduction. STATCOM uses force commutating devices like IGBT or MOSFET to control reactive power flow through a power network so that it increases stability of the power network.